2012
DOI: 10.1088/1674-1137/36/11/009
|View full text |Cite
|
Sign up to set email alerts
|

Study of a position-sensitive scintillator neutron detector

Abstract: The investigation of a novel thermal neutron detector is developed to fulfill the requirements of the high intensity power diffractometer (HIPD) at the Chinese Spallation Neutron Source (CSNS). It consists of two layers of 6LiF/ZnS(Ag) scintillators, two layers of crossed WLSF arrays, several multi-anode photo multiplier tubes (MA-PMT), and the matching readout electronics. The neutron detection efficiency of the scintilltors, the light transportation ability of the WLSF, and the spatial linearity of the reado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
0
16
1
Order By: Relevance
“…When the replacement percentage is 75%, the splitting tensile strength of recycled concrete approaches that of normal concrete, while the replacement percentage is 25% and 100%, the splitting tensile strength of recycled concrete is obviously lower than that of normal concrete with 12.7% and 24.8%, respectively, and when the replacement percentage is 50%, the tensile splitting strength is 5.7% higher than that of normal concrete. These results does not agree with those of Yang et al [19], who thought that the recycled concrete tensile strength is decreased with the increase of recycled coarse aggregate replacement percentage. However, these results are consistent with the quasi static compressive test results of Xiao et al [20], who found that when the recycled coarse aggregate replacement percentage was 50%, the compressive strength of recycled concrete was higher than that of normal concrete.…”
Section: The Test Resultscontrasting
confidence: 89%
“…When the replacement percentage is 75%, the splitting tensile strength of recycled concrete approaches that of normal concrete, while the replacement percentage is 25% and 100%, the splitting tensile strength of recycled concrete is obviously lower than that of normal concrete with 12.7% and 24.8%, respectively, and when the replacement percentage is 50%, the tensile splitting strength is 5.7% higher than that of normal concrete. These results does not agree with those of Yang et al [19], who thought that the recycled concrete tensile strength is decreased with the increase of recycled coarse aggregate replacement percentage. However, these results are consistent with the quasi static compressive test results of Xiao et al [20], who found that when the recycled coarse aggregate replacement percentage was 50%, the compressive strength of recycled concrete was higher than that of normal concrete.…”
Section: The Test Resultscontrasting
confidence: 89%
“…Total excision was performed in 54 cases out of 78 cases, (69.23%) of Sympson I in agreement of King"s study [24] as well as Solero and all [6] who respectively found Sympson I excision in 74 % and 96.5%. On the other hand, Liang Wu found Sympson I excision in 33.33% versus 66.67% Sympson II excision for cervical meningiomas because of the stranglehold of the vertebral arteries in the lesion [35,36] The using of cavitron is noted in (2 cases) 2.56% especially by Suzuki and Takeuchi [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . The using of laser and cavitron in 2 cases were noted by Roux and King [19][20][21][22][23][24] .…”
Section: -Surgical Managementmentioning
confidence: 99%
“…The internal resistance of GPTi (322.67 Ω) was also lower than that of UTi, indicating that G/PANI modification of the anode reduced the internal resistance of the entire MFC system. Since internal resistance is another important factor limiting the performance of MFCs for power generation [31,34], a reduction in internal resistance means an improvement in power generation of MFCs.…”
Section: G/pani Modification Of Anodementioning
confidence: 99%